Inertial Forces and Friction in Propulsion of a Rigid Body - Roman Starosta; Paweł Fritzkowski (Applied Sciences)
Inertially driven or vibration-driven capsule robots have recently attracted attention from various areas of science and engineering. The main advantage of such a mobile system is the lack of any external driving mechanism, which allows for an encapsulated construction and efficient operation in demanding environments. This study focuses on the conception of a mechanical system whose motion on a rough horizontal plane is caused only by the rotation of two internal masses. The mathematical model of the robot is presented in the non-dimensional form. The conditions for motion are formulated, and the working region of the system is specified. The active phase of the robot dynamics may include both forward motion and minor backward motion, or forward motion exclusively. Extensive numerical studies are conducted using two friction models. The numerical solutions to the dynamic problem are analyzed with regard to the total displacement and the average velocity per period of excitation. The interplay between model parameters is studied. The resulting maps on the parameter planes allow for substantial improvement in the robot performance. Moreover, it is demonstrated that the Stribeck effect occurring in the friction characteristics plays a positive role in the efficient motion of the system.